The Cambridge companion to Leibniz - Jolley, Nicholas (Cambridge companions to philosophy, 1994)
Gottfried Leibniz was a remarkable thinker who made fundamental contributions not only to philosophy, but also to the development of modern mathematics and science. At the centre of Leibniz's philosophy stands his metaphysics, an ambitious attempt to discover the nature of reality through the use of unaided reason. This volume provides a systematic and comprehensive account of the full range of Leibniz's thought, exploring the metaphysics in detail and showing its subtle and complex relationship to his views on logic, language, physics, and theology. Other chapters examine the intellectual context of his thought and its reception in the eighteenth century. New readers and nonspecialists will find this the most accessible and comprehensive guide to Leibniz currently available. Advanced students and specialists will find a conspectus of recent developments in the interpretation of Leibniz.